Long-term outcome after urinary diversion using the ileocecal segment in children and adolescents: complications of the efferent segment - Kosiba, Marina; Stein, Raimund (Journal of pediatric urology, 2016)
Summary - Introduction - Long-term outcomes are of special concern in children after urinary diversion. In a single institution study we evaluated retrospectively the long-term outcomes of urinary diversion in children, in whom the ileocecal segment had been used, in respect to complications of the efferent segment. - Methods - The Mainz pouch was used in 107 children for continent urinary diversion. Indications were neurogenic bladder (53%, 57/107), exstrophy-epispadias complex (25%, 27/107), malignancy (13%, 14/107), and others (9%, 9/107). Continent cutaneous diversion was performed in 95 patients, and 12 patients received bladder augmentation/substitution with a continent cutaneous stoma. As efferent segment, we used the in situ submucosally embedded appendix in 55/107, and an intussuscepted ileal nipple valve in 45/107 patients, other in seven patients. Complication rates and degree of satisfaction with urinary diversion were evaluated by assessing medical records and using follow-up questionnaires. - Results and discussion - The median follow-up time was 15.9 years (0.4-27.6 years). There was a significant difference between the stenosis rates of appendical stoma and the intussuscepted ileal nipple valve. In general, 38% of patients (41/107) with a continent cutaneous stoma developed a stoma stenosis at the skin level, with 41% (17/41) of those having recurrent stenoses (2-6×). Of the patients with an appendix stoma, 49% (27/55) developed a stenosis, compared with 20% (9/45) of those with an intussuscepted ileal nipple valve (p < 0.001). In an attempt to reduce the incidence of stenosis, we implemented use of the ACE stopper during the last 2 years, but whether this is successful is subject to further investigations. For surgical treatment of stoma stenosis, reanastomosis of the efferent segment to the skin (n = 37, re-stenosis rate 37%, [14/37]) was superior to endoscopic scar incision (n = 44, re-stenosis rate 59% [26/44], OR 2.4). The overall continence rate was 85% (91/107). At the latest follow-up, 89% (49/55) of patients with an appendix stoma and 82% (37/45) of those with an intussuscepted ileal nipple valve were completely continent. - Conclusion - The in situ submucosally embedded appendix and the intussuscepted ileal nipple valve are reliable continence mechanisms in the long-term median follow-up of nearly 16 years. The stomal stenosis rate is approximately double for the submucosal appendix, likely because of its smaller diameter in comparison with the ileal valve. Although we encountered a high overall rate of complications, the satisfaction rate with the diversion was high (99% [88/89] satisfied or very satisfied patients).
Gesehen am 16.07.2019